Pengaruh Kekuatan Otot Lengan dengan Menggunakan Dumbbell Terhadap Peningkatan Kemampuan Shooting pada Atlet Petanque - Rahma, Rahma; Ahmad, Ahmad; Dahlan, Firmansyah; Sihombing, Binsar Hasudungan; Nur, Suaib; Hidayat, Rachmat (Jurnal Porkes, 2025)
From initial observations, out of 12 shooting opportunities, only 5 balls hit the target. Weak arm muscles resulted in unstable, uncontrolled throws, ultimately reducing the effectiveness of the game. Therefore, a training method is needed to overcome this fundamental problem in order to improve athlete performance. This study aims to analyze the effect of arm muscle strength training using dumbbells on improving shooting ability in petanque athletes. The method used was a quasi-experiment with a one-group pretest-posttest design. A total of 15 athletes were selected as samples and given treatment in the form of 16 dumbbell training sessions. Shooting ability was measured before and after the treatment, and the data were analyzed using a paired sample t-test in the SPSS program. The results showed a significant improvement in shooting ability. The pretest average score of 24.67 increased to 30.33 in the posttest. The hypothesis test produced a t-count value of 10.845 > t-table 1.761 with a significance of 0.000. The conclusion of this study is that dumbbell training has been proven to significantly increase arm muscle strength, which ultimately contributes to improved accuracy, stability, and control in the shooting ability of Palopo City petanque athletes. This training is recommended to be integrated into the program.